REGIONAL BRANDING OF WESTERN BALKANS THROUGH SUSTAINABLE TOURISM - Cela, Sonila; Hysa, Xhimi; Duman, Teoman; Zenelaj, Besjon (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
Western Balkans (WB) is emerging from an unfortunate recent past which destroyed social structures and the uniform identity of the region. WBs is, historically, known as a region of diversity and impeccable natural beauty. Despite a visible need to take a holistic approach for WBs tourism marketing, a research-based strategy has yet to be defined and implemented for future action in the region. There are few current studies dealing with regional branding, brand identity and sustainable tourism in WB, and most of them do not offer a holistic approach in integrating the identification of tourism (through destination brand identity) and the promotion of tourism (through destination brand positioning). This research, therefore, aims to reach a framework for a holistic tourism marketing effort for the region by focusing on how WBs should create a regional destination image for a stronger destination marketing in the future. As one of the pioneering research studies on the subject, the research holds an exploratory approach, and the research question is answered based on qualitative SWOT analysis data from experts in the region. Findings from the qualitative research point to strong tourism potential in the region, which supports a strong argument for a sustainable tourism agenda of the WBs. Interviewed experts considered the lack of big-branded hotels as a weakness, due to the low levels of accommodation capacities, while confirming a weak strategic positioning of the region as a unified whole. Other results demonstrate that the region can also offer unique agrotourism products. This study concludes with a proposed “Sustainability–SWOT-based Destination Branding Model” as a guide for future tourism development and promotion efforts.